The NIV application commentary : Philippians - Thielman, Frank (Grand Rapids, Mich. : Zondervan Publishing House, 1995)
Most Bible commentaries take us on a one-way trip from the twentieth century to the first century. But they leave us there, assuming that we can somehow make the return journey on our own. In other words, they focus on the original meaning of the passage but don't discuss its contemporary application. The information they offer is valuable but the job is only half done! The NIV Application Commentary Series helps us with both halves of the interpretative task. This new and unique series shows readers how to bring an ancient message into modern context. It explains not only what the Bible meant but also how it can speak powerfully today.
Series introduction -- General editor's preface -- Author's preface -- Introduction -- Annotated bibliography -- Text and commentary on Philippians -- Scripture index.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Bible. N.T. Philippians - Commentaries; Commentaries